Effects of ternary alloy additions on the microstructure of highly immiscible Cu alloys subjected to severe plastic deformation: An evaluation of the effective temperature model. (15th May 2019) - Verma, Nisha; Pant, Nirab; Beach, John A.; Ivanisenko, Julia; Ashkenazy, Yinon; Dillon, Shen; Bellon, Pascal; Averback, Robert S.
Abstract: Phase evolution in dilute, strongly immiscible Cu-Mo, Cu-Mo-Ni, and Cu-Mo-Ag alloys during severe plastic deformation at low-temperature has been experimentally investigated. For the Cu95 Mo05 alloy, Mo nanoparticles are formed, ∼10 nm in diameter, as part of a steady state microstructure, with less than ∼1 at.% Mo dissolved in the matrix. Addition of 10 or 20 at.% Ni to this binary alloy results in a significant increase in the Mo solubility, whereas comparable additions of Ag has a corresponding little effect. The steady state microstructures of alloys during ball milling of elemental powders are very similar to those during HPT processing of initially homogeneous solutions. The results are discussed in terms of an effective temperature model. Model MD simulations are presented to help relate the predictions of the effective temperature model to atomistic mechanisms. Graphical abstract: Image 1